Exploiting Polythiophenyl‐Triazine‐Based Conjugated Microporous Polymer with Superior Lithium‐Storage Performance. Issue 9 (1st April 2020) - Ren, Shi‐Bin; Ma, Wenyan; Zhang, Chong; Chen, Lei; Wang, Kai; Li, Rong‐Rong; Shen, Mao; Han, De‐Man; Chen, Yuxiang; Jiang, Jia‐Xing
Abstract: Conjugated microporous polymers (CMPs) have been heralded as promising energy‐storage materials with advantages such as chemical flexibility, porous structure, and environmentally friendliness. Herein, a novel conjugated microporous polymer was synthesized by integrating triazine, thiophene, and benzothiadiazole into a polymer skeleton, and the Li + ‐storage performance for the as‐synthesized polymer anode in Li‐ion batteries (LIBs) was investigated. Benefiting from the inherent large surface area, plentiful redox‐active units, and hierarchical porous structure, the polymer anode delivered a high Li + storage capacity up to 1599 mAh g −1 at a current rate of 50 mA g −1 with an excellent rate behavior (363 mAh g −1 at 5 A g −1 ) and a long‐term cyclability of 326 mAh g −1 over 1500 cycles at 5 A g −1, implying that the newly developed polymer anode offers a great prospect for next‐generation LIBs. Abstract : Three for one : A conjugated microporous polymer consisting of triazine, thiophene, and benzothiadiazole, as anode for lithium‐ion batteries shows a high Li + storage capacity of 1599 mAh g −1 and excellent rate performance as well as long‐term cyclability.